2022
DOI: 10.1093/eurheartj/ehac037
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell-derived tetrahydrobiopterin prevents aortic valve calcification

Abstract: Aims Tetrahydrobiopterin (BH4) is a critical determinant of the biological function of endothelial nitric oxide synthase. The present study was to investigate the role of valvular endothelial cell (VEC)-derived BH4 in aortic valve calcification. Methods and results Plasma and aortic valve BH4 concentrations and the BH4:BH2 ratio were significantly lower in calcific aortic valve disease patients than in controls. There was a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 57 publications
0
16
0
1
Order By: Relevance
“…GTP cyclohydrolase 1 (GCH1) is also identified as a conditioner of ferroptosis [ 16 , 17 ]. BH4 is capable of trapping lipid peroxyl radicals with GCH1 mediating the rate-limiting reaction in its biological synthesis [ 99 ]. Specifically, the GCH1-BH4 system suppresses ferroptosis through GCH1-mediated generation of CoQH2 as well as via the radical-trapping antioxidant ability of BH4 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…GTP cyclohydrolase 1 (GCH1) is also identified as a conditioner of ferroptosis [ 16 , 17 ]. BH4 is capable of trapping lipid peroxyl radicals with GCH1 mediating the rate-limiting reaction in its biological synthesis [ 99 ]. Specifically, the GCH1-BH4 system suppresses ferroptosis through GCH1-mediated generation of CoQH2 as well as via the radical-trapping antioxidant ability of BH4 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been described that patients with severe valvular stenosis have increased circulating metabolites related to NO metabolism and that the levels of these metabolites normalize when the valve is replaced [ 37 ]. In addition, endothelial BH4, a cofactor necessary for eNOS-induced NO production, can prevent osteoblastic differentiation of VICs [ 38 ]. We previously reported that ILK facilitates eNOS function by promoting BH4 bioavailability [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased alkaline phosphatase activity is associated with increased calcified nodules and calcium and phosphorus deposition ( 47 ). In another study, Liu et al discovered that alkaline phosphatase plays an important role in the development of aortic valve fibrosis ( 48 ). In the present study, alkaline phosphatase was also found to be associated with the pathogenesis of CAVS (P=0.006), which was consistent with the abovementioned findings, suggesting that it could be involved in the occurrence of CAVS through various mechanisms and could be an important predictor of the disease.…”
Section: Discussionmentioning
confidence: 99%